Riwayat Pemberian Asi Ekslusif, Mp-Asi Dengan Kejadian Stunting Pada Anak Usia 24-60 Bulan Di Puskesmas Sangkub Kabupaten Bolaang Mongondow Utara - Vera T. Harikedua; Yohanis Tomastola; Irza N. Ranti; Aklianto Kamboa (Jurnal GIZIDO, 2019)
Stunting is a condition of failure to thrive in children under five (babies under five years old) as a result of chronic malnutrition so that the child is too short compared to his age. MP-ASI (Complementary Food for Mother's Milk) is food or drink that contains nutrients, given to children aged 6-24 months to meet nutritional needs other than breast milk. The purpose of this study was to determine the history of exclusive breastfeeding and MP-ASI with stunting in the working area of ​​Sangkub Health Center.This type of research is Observational using a cross sectional design.. Data collection was obtained from the results of measurements of children's height using microtoise and interviews using questionnaires. Data analysis using statistical software with Chi Square test type with a significant value (α) = 0.05. The results of the study with statistical tests show a sample with a short category that is 78% and a very short category of 22%, a sample that gets Exclusive ASI is 29.3% and who does not get Exclusive ASI 70.7%, a sample that gets MP-ASI> 6 months namely 29.3% and those receiving MP-ASI <6 months is 70.7%. A history of exclusive breastfeeding with a Stunting event with a p value = 0.039 and a history of MP-ASI with a Stunting event with a p value = 0.039. There is a relationship between the history of exclusive breastfeeding and MP-ASI with the occurrence of stunting in the working area of ​​the Sangkub Community Health Center, North Bolaang Mongondow District.